The Influence of Leadership Style and Management of Boarding School on Community Interest (Comparative Study between Modern Islamic Boarding Schools and Salafi Islamic Boarding Schools in Rangkasbitung Lebak) - Rumbang Sirojudin (AL-ISHLAH: Jurnal Pendidikan, 2022)
There have been Islamic boarding schools in Indonesia for as long as there have been schools in general, and they play a crucial role in the country's educational system. The researchers set out to learn how different types of leadership and administration at Islamic boarding schools affect students' level of community interest. With a 2 x 2 factorial experimental design, this study used the ex post facto method, sometimes known as a comparative causal relationship. A questionnaire was employed as the data collection technique for this investigation. Descriptive and inferential statistics were employed to examine the data. Path A two-way ANOVA revealed that Fcount is higher than Ftable (Fcount = 5.81 Ftable (0.05; 1:116) = 3.92), indicating that count variables contributed more to the overall variation in this path than did table variables. For some reason, in Row B, we see that Fcount is larger than Ftable (Fcount = 8.73 Ftable (0.01; 1:116) = 6.86). Larger AB interactions are found using Fcount (Fcount = 140.51 Ftable (0.01; 1:116) = 6.86) when looking at rows A * B. Findings from this research indicate a positive correlation between leadership styles and community interest. Additionally, modern Islamic boarding schools and Salafi Islamic schools have vastly different approaches to administration.